2021
DOI: 10.1159/000516212
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Plastic Cannulae Compared with Metal Needles in the Initial Use of an Arteriovenous Fistulae in Incident Hemodialysis Patients: A Randomized Controlled Study

Abstract: <b><i>Introduction:</i></b> Successful cannulation of an arteriovenous fistula (AVF) is important in patients starting hemodialysis (HD). Metal needles have been used for decades, but the usefulness of plastic cannulae has recently been demonstrated as a new technique. <b><i>Methods:</i></b> This was a prospective, randomized, open-label study of incident HD patients. Eligible patients were randomized into 2 groups in a 1:1 ratio (<i>n</i> = 45/group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Previous randomised controlled studies have successfully shown that plastic cannula can improve cannulation outcomes (Choi et al, 2021;Marticorena et al, 2018). In these studies, the authors recruited a targeted number of nurses with advanced levels of competency to undertake all cannulations, with one also using the adjunct of point-of-care ultrasound guided cannulation with all events (Marticorena et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous randomised controlled studies have successfully shown that plastic cannula can improve cannulation outcomes (Choi et al, 2021;Marticorena et al, 2018). In these studies, the authors recruited a targeted number of nurses with advanced levels of competency to undertake all cannulations, with one also using the adjunct of point-of-care ultrasound guided cannulation with all events (Marticorena et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The nurses' survey responses indicated that they would like to have a preference to use either device, based on individual patients' circumstances. Whilst the outcomes of previous studies on the use of plastic cannulae in cannulation of AVF is promising in relation to the reduction of; interventional procedures (Marticorena et al, 2018), miscannulations (Choi et al, 2021) and aborted haemodialysis sessions, there still remains a lack of empirical evidence on the topic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations